MENDUDUKKAN FATWA MAJELIS ULAMA INDONESIA SEBAGAI DOKTRIN PERUNDANG-UNDANGAN - sarip, sarip sarip (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2019)
The position of the Fatwa of the MUI is not in the order of laws and regulations as Indonesian formal law. The fatwas decided by the MUI sometimes cause controversy in the midst of society, some see it as the mouthpiece of the authorities, and there are also people who judge it as inconsistence. Indonesian legislation in the development of national law politics prioritizes formal instruments as stipulated in national law when compared with jurisprudence and living law. Using a descriptive method and a legislative approach regarding the subject matter. The fatwa of the MUI as a legal doctrine is a legal research that has the substance of Fatwa, which is a process to find legal doctrines in response to legal issues faced. The law cannot be separated from the community, so the living law that dominates life even though it has not been included in the state law. Legal doctrine is said to be one source of law, even though it is not listed in Indonesian formal legislation. The Fatwa MUI is a means of placing in order to know the status of the state of the MUI Fatwa as a legal doctrine. The word occupation can also be interpreted as placing the MUI Fatwa as one of the sources of law in the sense of methyl in the form of legal doctrine and its power in influencing the policy of the formation of legislation in Indonesia. Not all Fatwa MUI can be regarded as doctrines if the MUI Fatwa does not consider the philosophical, sociological, and juridical reasons or the MUI Fatwa is made arbitrarily. Keywords: Occupy, Fatwa, MUI, Doctrine, law